Design, synthesis and bio-evaluation of C-1 alkylated tetrahydro-β-carboline derivatives as novel antifungal lead compounds. Issue 3 (1st February 2020) - Singh, Rahul; Jaisingh, Aanchal; Maurya, Indresh K.; Salunke, Deepak B.
Graphical abstract: Abstract: The field of antifungal agent has become static and development of resistance by the pathogen as well as limited clinical efficacy of marketed drugs demand the constant development of new antifungals. The presence of hydrocarbon chain of specific length linked with various different heterocycles was found to be an important structural feature in various antifungal lead compounds. Based on the prominent antimicrobial activity of β-carboline derivatives, a set of C1 alkylated tetrahydro-β-carboline derivatives were proposed to be active against fungi. To validate and confirm the role of suitable alkyl chains linked to a β-carboline scaffold, few related analogues having C1 aryl substituents were also synthesized in one step via classic Pictet-Spengler reaction. The synthesized library was evaluated for its antifungal activity against C. albicans, C. krusei, C. parapsilosis, C. kefyr, C. glabrata, C. tropicalis and C. neoformans. One of the library members (compound 12c ), with n -alkyl chain of eight carbons exhibited potent antifungal activity against C. glabrata and C. kefyr . The lead compound, being selectively toxic also demonstrated prominent synergy enhancing the potency of antifungal drugs up to 10-fold. The time kill kinetic studies confirmed the efficacy of compound 12c, where the results obtained were comparable to that of Amp B. FE-SEM analysis revealed the increased asymmetry, disintegration and roughness of cell surface which could be because of the possible interaction of compound 12c at membrane level or interference in cell wall structure. Apoptosis/necrosis detection assay confirmed the significant apoptotic activity in C. glabrata cells after 12c treatment which was responsible for the rapid killing of C. glabrata cells.